2013
DOI: 10.1007/s13278-013-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

Bursty egocentric network evolution in Skype

Abstract: In this study we analyze the dynamics of the contact list evolution of millions of users of the Skype communication network. We find that egocentric networks evolve heterogeneously in time as events of edge additions and deletions of individuals are grouped in long bursty clusters, which are separated by long inactive periods. We classify users by their link creation dynamics and show that bursty peaks of contact additions are likely to appear shortly after user account creation. We also study possible relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…3.10 indicate a heterogenous pattern of activity and, despite the exponential cut-off, small inter-event times are significantly more probable than an exponential distribution. This is in line with previous research that has shown that the nature of link creation process in online social networks is broad and follows a power-law distribution (Gaito et al 2012;Kikas et al 2012;. In these studies the bursty behavior of tie creation is usually associated to an acceleration (or exploration) phase in which tie formation rapidly increases.…”
Section: Dynamics Of Tie Creation/removalsupporting
confidence: 90%
See 1 more Smart Citation
“…3.10 indicate a heterogenous pattern of activity and, despite the exponential cut-off, small inter-event times are significantly more probable than an exponential distribution. This is in line with previous research that has shown that the nature of link creation process in online social networks is broad and follows a power-law distribution (Gaito et al 2012;Kikas et al 2012;. In these studies the bursty behavior of tie creation is usually associated to an acceleration (or exploration) phase in which tie formation rapidly increases.…”
Section: Dynamics Of Tie Creation/removalsupporting
confidence: 90%
“…This filtering is because the activity of nodes that subscribed/unsubscribed just before/after Ω may introduce spurious effects in the analysis of edge dynamics. Specifically, we would observe a rapid growth of their social network at the beginning of the observation window or a fast dissolution at its end (Gaito et al 2012;Kikas et al 2012). The latter filtering results in the removal of about the 17% of nodes and the 37% of reciprocated links.…”
Section: Daysmentioning
confidence: 99%
“…Multiple techniques have been proposed to discover social or topical sub-groups within ego-networks [53,37,40,13], but with little attention to the dynamics of their growth. Kikas et al conducted one of the few studies touching upon the the temporal evolution of ego-networks, using a dataset of Skype contacts [30]. They find that most edges are added in short bursts separated by long inactivity intervals.…”
Section: Related Workmentioning
confidence: 99%
“…Creation of links is not uniform in time. Previous literature found evidence that, globally, the creation of links happens in bursts [32,30]. At a local level, we aim to learn how often and in which phases of the ego-network life users select new neighbors.…”
Section: Temporal Activitymentioning
confidence: 99%
See 1 more Smart Citation